Developing an innovative management model to enhance teaching and research effectiveness in Vietnamese educational institutions - Kien, Phan Trung; Khanh, Mai Quoc; Tinh, Tran Trung; Yen, Nguyen Thi Hai (Edelweiss Applied Science and Technology, 2025)
This study aims to develop a comprehensive management model to improve teaching and research effectiveness in Vietnamese universities. The purpose of the research is to examine key factors influencing academic performance through the lens of rational choice theory and social exchange theory. A mixed-methods design, combining quantitative surveys and qualitative interviews, was used to gather data from 200 faculty members across seven universities and 20 in-depth interviews with educators, administrators, and policymakers. The findings indicate that institutional support is crucial to educational effectiveness, with universities receiving strong administrative backing showing higher teaching quality and research engagement. Faculty training emerged as a critical factor in improving pedagogical outcomes, while challenges such as resistance to digital transformation and insufficient research incentives were identified. The study concludes that enhancing faculty development, adopting flexible governance models, and promoting interdisciplinary research are essential for improving educational performance. Practical implications include investing in digital transformation and fostering international competitiveness. Future research should investigate the long-term impact of digital technologies and AI on higher education governance.